ANALISIS MEKANISME PENGHIMPUNAN DANA TABUNGAN HAJI DENGAN AKAD MUDHARABAH PADA BANK BTN KCPS PROBOLINGGO - Najib, Ainun; Nasrifah, Maula; Liam, Liam (universitas Islam Zainul Hasan Genggong, 2024)
This research will discuss the analysis of the mechanism for collecting hajj savings funds using a Mudharabah agreement at BTN KCPS Probolinggo. With the aim of finding out more about the mechanism for collecting Hajj savings funds with a Mudharabah agreement at BTN KCPS Probolinggo. The research method is descriptive qualitative and data is obtained through observation, interviews and documentation, tested with credibility tests and analyzed from data collection to reporting. The results of this research show that the Mudharabah Agreement which is used to collect funds is also very helpful for customrs in deciding to save for hajj at BTN KCPS Probolinggo, where the sharia system is currently starting to develop in Indonesia. With the existence of this hajj savings product at BTN, of course, using the Mudharabah contract as a reference, there are many things that can be obtained by the customers themselves, such as helping to ease the preparation and carrying out of the hajj through sharia-based fund management, free opening fees, no monthyl administration, and customers can get ATM card fasilities that can be used by VISA providers.